1999
DOI: 10.1177/070674379904400308
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a French Version of the Dissociative Experiences Scale in a Rape-Victim Population

Abstract: During validation of a French version of the DES, the study showed that dissociation is considerably linked to rape-trauma victim populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
2

Year Published

2004
2004
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 74 publications
(18 citation statements)
references
References 8 publications
0
16
0
2
Order By: Relevance
“…Three-factor extractions have generally been reported in the literature (Stockdale, Gridley, Balogh, & Holtgraves, 2002), including amnesia (6 items), depersonalization (6 items) and absorption (16 items). In the present study, we used the French version of the DES, which has been shown to have good reliability as well as the same three-factor solution as the English version in a population of rape victims (Darves-Bornoz, Degiovanni, & Gaillard, 1999). For each item, respondents indicate percentage of the time a certain experience occurs, based on a 21-point scale (from 0% to 100% in 5% increments).…”
Section: Dissociative Experiences Scale (Des)mentioning
confidence: 99%
“…Three-factor extractions have generally been reported in the literature (Stockdale, Gridley, Balogh, & Holtgraves, 2002), including amnesia (6 items), depersonalization (6 items) and absorption (16 items). In the present study, we used the French version of the DES, which has been shown to have good reliability as well as the same three-factor solution as the English version in a population of rape victims (Darves-Bornoz, Degiovanni, & Gaillard, 1999). For each item, respondents indicate percentage of the time a certain experience occurs, based on a 21-point scale (from 0% to 100% in 5% increments).…”
Section: Dissociative Experiences Scale (Des)mentioning
confidence: 99%
“…Participants were also asked to complete a French version (Darves-Bornoz et al, 1999) of the Dissociative Experiences Scale (DES; Bernstein & Putnam, 1986). The DES is a 28-item scale, developed to obtain a self-reported measure of the frequency of experiencing dissociative symptoms such as derealization and depersonalization.…”
Section: Methodsmentioning
confidence: 99%
“…The PTSD symptomatology, dissociative dimension and psychiatric comorbidities were evaluated by a trained psychiatrist (W.E.H.) using the Clinical Administered PTSD Scale (CAPS), 15 the Dissociative Experiences Scale (DES) 16 and the Mini International Neuropsychiatric Interview (MINI 5.0.0), respectively. 17,18 Participants received full details about the experimental protocol and provided written informed consent before the beginning of the experiments.…”
Section: Participantsmentioning
confidence: 99%